Chemical characteristics of three-stage fog water in an agricultural city in China - Ge, Panyan; Fan, Shuxian; Wang, Yuan; Zhang, Sirui; Wu, Haopeng; Shao, Naifu; Zu, Fan (Frontiers in Environmental Science, 2022)
To investigate the relationships among the chemical compositions of fog droplets, atmospheric pollutants, and the fog microphysical characteristics, four fog cases were sampled in a comprehensive field experiment conducted at the Donghai site in an agricultural city, China, in the winter of 2020. The pH, electrical conductivity (EC), total ion concentration (TIC), and chemical compositions of the fog water were all size-dependent. High concentrations of non-sea-salt calcium (nssCa2+) and NH4+ led to the alkaline pH of 6.13-7.32. The TIC of fog water was relatively high, especially in small droplets of diameter within 4-16 μm (463527.9 μeq/L). The relatively high NO2- concentration was also found in the fog water, dominated by the non-homogeneous chemical reaction between NO2 and fog droplets. An interesting finding is that the TIC of fog water measured on December 12 was much higher than that measured on December 11. Compared to the first fog, the stronger thermal inversion and local emissions led to the higher concentration of atmospheric particles in the second fog. Generally, the relatively high concentration of atmospheric particles resulted in a large number of small-sized droplets, which had fast liquid-phase oxidation reaction rates and high gas-liquid conversion efficiencies, leading to a higher TIC in the fog water during the second fog.